INTEREST GROUP COLLABORATIVE SYMPOSIUM: A FEMINIST LENS ON WOMEN'S AGING USING QUALITATIVE METHODS. (11th November 2018) - Harrison, T; Hooyman, N R
Abstract: The purpose of this symposium, brought together by the Women's Issues Interest Group and the Qualitative Research Interest Group, is to promote discussions about gender and older women's lives. Drawing equally from both interest groups, the panel includes four papers that analyze aging through the late life lens of women, examining dynamics that affect their aging experience. The researchers use feminist theory to frame explorations of a diverse group of older women's lives. The papers investigate the ways women feel the physicality of aging while meeting their perceived societal and family roles. Research methods include grounded theory, narrative analysis, and discursive methodologies. First, Smith presents a grounded theory study of older mother's late life caregiving to adult children. This is followed by Harrison's narrative analysis of older Mexican American women's self-management of their disabilities. Third, Koren's grounded theory study of late-life re-partnering after widowhood among women involved in new relationships, in relation to men, is presented. The fourth paper by Davis is a discourse analysis of stroke talk about older women; and the final paper is by Simpson and Harrison. It is an ethnographic analysis of how older women with mental illness negotiate personal resources when faced with multiple stigmatizing circumstances. The discussant, Nancy Hooyman, is a pioneer in feminist gerontology for her research and advocacy work surrounding family and end of life social work practice. She will guide the feminist discussion of the panel's work.